Isocitrate dehydrogenase mutation is frequently observed in giant cell tumor of bone. Issue 6 (June 2014) - Kato Kaneko, Mika; Liu, Xing; Oki, Hiroharu; Ogasawara, Satoshi; Nakamura, Takuro; Saidoh, Noriko; Tsujimoto, Yuta; Matsuyama, Yuka; Uruno, Akira; Sugawara, Masato; Tsuchiya, Takashi; Yamakawa, Mitsunori; et al.
<x xml:space="preserve">Abstract</x> Giant cell tumors of bone (GCTB) are benign and locally destructive tumors that include osteoclast‐type multinuclear giant cells. No available treatment is definitively effective in curing GCTB, especially in surgically unresectable cases. Isocitrate dehydrogenase (IDH) mutations have been reported not only in gliomas and acute myeloid leukemias, but also in cartilaginous tumors and osteosarcomas. However, IDH mutations in GCTB have not been investigated. The IDH mutations are remarkably specific to arginine 132 (R132) in IDH1 and arginine 172 (R172) or arginine 140 (R140) in IDH2; IDH1/2 mutations are known to convert α‐ketoglutarate to oncometabolite R(‐)‐2‐hydroxyglutarate. We recently reported that the most frequent IDH mutation in osteosarcomas is IDH2‐R172S, which was detected by MsMab‐1, a multispecific anti‐IDH1/2 mAb. Herein, we newly report the IDH mutations in GCTB, which were stained by MsMab‐1 in immunohistochemistry. DNA direct sequencing and subcloning identified IDH mutations of GCTB as IDH2‐R172S (16 of 20; 80%). This is the first report to describe IDH mutations in GCTB, and MsMab‐1 can be anticipated for use in immunohistochemical determination of IDH1/2 mutation‐bearing GCTB.